Teaching English Language Arts to English Language Learners Preparing Pre-service and In-service Teachers - de Oliveira, Luciana; Shoffner, Melanie; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book focuses on the ways in which English language arts pre-service and in-service teachers have developed - or may develop - instructional effectiveness for working with English language learners in the secondary English classroom. Chapter topics are grounded in both research and practice, addressing a range of timely topics including the current state of ELL education in the ELA classroom, and approaches to leveraging the talents and strengths of bilingual students in heterogeneous classrooms. Chapters also offer advice on best practices in teaching ELA to multilingual students and ways to infuse the secondary English teacher preparation curriculum with ELL pedagogy. Comprehensive in scope and content and examining topics relevant to all teachers of ELLs, teacher educators and researchers, this book appeals to an audience beyond ELA teachers and teacher educators. Luciana C. de Oliveira is Associate Professor in the Department of Teaching and Learning in the School of Education and Human Development at the University of Miami, Florida. Her research focuses on issues related to teaching English language learners (ELLs) at the K-12 level. Melanie Shoffner is Associate Professor of English Education at Purdue University in West Lafayette, Indiana, where she holds a joint appointment in the Departments of English and Curriculum & Instruction. Focusing on secondary English teacher preparation, her research explores issues of reflective practice, dispositional development and meaningful integration of technology.
- Introduction -- Chapter 1: Addressing the Needs of English Language Learners in English Education -- Chapter 2: ELL Pedagogy in the English Methods Class: Collaborative Planning as a Component of Preservice Teacher Preparation -- Chapter 3: Learning to Teach ELLs through ELA Methods: Findings from a National Survey -- Chapter 4: Working with ELLs in the Mainstream ELA Classroom through Collaboration and Two-Way Content-Based Instruction -- Chapter 5: Humanizing the Core: English Language Learners and Culturally-Sustaining Young Adult Literature -- Chapter 6: Positive Positions: Preparing Teachers to Respond to the Writing of ELL Students -- Chapter 7: "But There's Gotta be a Strength": Toward the Equitable Assessment of the Writing of Emerging Bilingual Students -- Chapter 8: Filling the Gap: L2 Grammar and Assessment Preparation for ELA teachers -- Chapter 9: Learning to use Systemic Functional Grammar to Teach Literary Analysis: Views on the Effectiveness of a Short Professional Development Workshop -- Chapter 10: "It's Just Really Relevant to Them": One School District's Efforts to Teach ELA Credit-Bearing Newcomer ESOL Courses.
Keywords: Multilingualism; Language and languages-Study and; English language; Applied linguistics